An observational study of haemophilia patients attending a tertiary care centre in West Bengal - Khuntdar, Bidyut Kumar; Patra, Kajal Kumar; Sau, Manabendra; Madhwani, Kishore P (Asian Journal of Medical Sciences, 2022)
Background: Haemophilia is the most common inherited coagulation disorders transmitted by X-linked recessive fashion affecting the males and females are the carriers of the disease. Haemophilia is distributed worldwide and has heterogeneous presentation depending on its severity starting from neonatal period. Knowledge of spectrum of the presentation of haemophilia helps in early diagnosis and planning of management. Aims and Objectives: This study aims to evaluate the socio-demographic profile of the patients, clinical presentations, epidemiological profiles, and the outcomes of the hemophilic patients in a tertiary care teaching hospital in West Bengal. Materials and Methods: This study was a prospective, observational, single center study conducted in the Pediatrics haemophilia treatment center at Midnapore Medical College, Paschim Medinipore from May 2020 to April 2021. Detailed history was taken and recorded in a predesigned pro forma Case Record Form. Analyses were done only after completion of CRF of the last patient. Statistical analyses were performed using SPSS version 20.0 software. Continuous variables were compared by Paired t-test. Dichotomous events were analyzed using the Fisher’s exact test and Chi-squared Test. Statistical significance was defined as P<0.05. Results: Mean age of children was 93.64 months (SD 6.38). All children of haemophilia were male. This study noted that majority of patients of haemophilia were staying at rural area (67.19%) and rest at urban area (32.81%). BMI of majority children was within normal limit (51.56%), followed by underweight children (32.81%), overweight children (12.50%), and obese child (3.13%). Factor assay showed that 51 children (79.69%) had severe factor deficiency and 13 children (20.31%) had moderate factor deficiency. Positive family history was seen in 41 children (64.06%), and rest 23 children (35.94%) had no family history of haemophilia or any other bleeding disorder. Majority of patients (26 patients) came with their first bleed during infancy (40.63%), 21 children presented between the age of >12 months to ≤24 months (32.81%). Bruises were the most common presentation (37.50%), followed by joint bleeding (31.25%), muscle bleed (10.94%), and gum bleeding (7.81%). Conclusion: Facility of counseling for children of hemophilia is required at regular interval (trimester wise/semester wise) with the aim to enhance the knowledge of personal care, treatment, and to boost up themselves for their academics, activities, etc.